Daddy is a cozy hug - Greene, Rhonda Gowler (Walker & Co. : Distributed to the trade by Macmillan, 2009)
A child celebrates all of the wonderful things a father can be throughout the year, from a wiggling fish in summer to a warm blanket in winter.